A Prominent Representative of the New Generation of Ukrainian Physicists (to the 60th birthday of Ihor Mryglod) - Yukhnovskii, I. R.; Bar’yakhtar, V. G.; Bakai, A. S.; Loktev, V. M.; Yatskiv, Ya. S.; Zagorodny, A. G.; Bryk, T. M.; Derzhko, O. V.; Folk, R.; Holovatch, Yu. V.; et al. (Ukrainian Journal of Physics, 2020)
-